THE POTENTIAL UTILIZATION OF COFFEE WASTE OF PT JAVABICA INTO BIO-BRIQUETTE AS ENVIRONMENTALLY-FRIENDLY FUEL - Joshua Luke Tandiono; Sri Endah A. (BRIN, 2020)
The coffee industry produces a large amount of waste in the form of coffee grounds, which is about 45% of the processed coffee beans. This research aims to study the potential of waste produced by the coffee industry as an environmentally friendly alternative fuel (green energy) in the form of biomass briquettes. The results show that coffee waste briquettes have a fairly good performance as fuel, are easily burnt, and have an energy content that is almost the same as dry wood. By using the “hot pressing” method in the mechanical pressing machine, bio briquettes with a fairly good density and strength level can be obtained. The briquettes have a heating value of 5169 – 5500 kcal/kg at water content of 12-12.5%, and a density of 0.35 – 0.86 g/cm3. Keywords: Bio-briquettes; Biofuel; Used Coffee Grounds; Hot Pressing; Environmentally Friendly; Renewable Energy